Musical Revitalization of Lamalera’s Ritual, Barter, and Lia Asa Usu Poetry - Maria Elerina Douk Tunti; Djoko Suhardjanto; Setianingtyas Honggowati; Wahyu Widarjo; Domingos Flaviono Belo Corriera Freitas (Institut Seni Indonesia Yogyakarta, 2026)
This study explores the interconnection between the Lefa ritual and the barter system in Wulandoni, which together form the foundational pillars of identity and a unique cultural heritage, as reflected in the Lia Asa Usu poetry chants of the Lamalera community in Lembata Regency, East Nusa Tenggara. A balanced relationship between marine life, social order, and spirituality—rooted in ancestral values—actively shapes the Lamalera identity. The Lia Asa Usu poetry serves as an essential means of instilling ecological ethics while guiding the community’s social, economic, and spiritual behavior. Modernization presents significant challenges to the sustainable transmission of Lamalera’s intangible cultural heritage. Therefore, this study aims to analyze the relationships among Lia Asa Usu poetry, cultural identity, and opportunities for revitalization through contemporary art, particularly music. Using a practice-based research approach, this study combines ethnographic rigor with the process of music creation. The Lia Asa Usu poetry is treated as a moral and historical archive, and is then interpreted into a composition that takes its structure from the emotional narratives of the Lamalera community, including the sound of waves and the rhythm of fishermen’s oars. The results demonstrate that the musical transformation of the poetry produces a new form that combines local tetratonic melodies and repetitive rhythmic patterns. This structure builds emotional and spiritual bridges that strengthen intergenerational connections and affirm cultural identity. The study also found a strong connection between the exodus narrative in the poetry, the origins of barter practices in Wulandoni, and Lamalera’s maritime identity. These findings emphasize that music functions not only as an aesthetic expression but also as an essential medium for transmitting core cultural values, ancestral migration history, coastal living ethics, and spiritual connections to the sea. In conclusion, music inspired by Lia Asa Usu effectively preserves tradition while bridging it to the younger generation.